Optothermal Needle‐Free Injection of Vaterite Nanocapsules - Denis Kislov; Daniel Ofer; Andrey Machnev; Hani Barhom; Vjaceslavs Bobrovs; Alexander Shalin; Pavel Ginzburg (Advanced Science, 2024)
Abstract The propulsion and acceleration of nanoparticles with light have both fundamental and applied significance across many disciplines. Needle‐free injection of biomedical nano cargoes into living tissues is among the examples. Here a new physical mechanism of laser‐induced particle acceleration is explored, based on abnormal optothermal expansion of mesoporous vaterite cargoes. Vaterite nanoparticles, a metastable form of calcium carbonate, are placed on a substrate, underneath a target phantom, and accelerated toward it with the aid of a short femtosecond laser pulse. Light absorption followed by picosecond‐scale thermal expansion is shown to elevate the particle's center of mass thus causing acceleration. It is shown that a 2 µm size vaterite particle, being illuminated with 0.5 W average power 100 fsec IR laser, is capable to overcome van der Waals attraction and acquire 15m sec−1 velocity. The demonstrated optothermal laser‐driven needle‐free injection into a phantom layer and Xenopus oocyte in vitro promotes the further development of light‐responsive nanocapsules, which can be equipped with additional optical and biomedical functions for delivery, monitoring, and controllable biomedical dosage to name a few.